1997
DOI: 10.1046/j.1365-2168.1997.02556.x
|View full text |Cite
|
Sign up to set email alerts
|

Indications and results of local treatment of rectal cancer

Abstract: Patients with pT1 rectal tumours represent a suitable group for local treatment because of the acceptability of the procedure and the low recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
20

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 27 publications
3
54
1
20
Order By: Relevance
“…In contrast the results reported using TEM show a recurrence rate between 3 and 7% with the 5.6% for the adenoma cases of our series pubished in 2004, being well in accordance with previous studies (Palma et al, 2004). The overall morbidity rate for conventional transanal surgery in reported series varies from 0 to 14.5%, compared with 6% reported in the largest series of a total of 318 adenomas treated by Mentges (Mentges et al, 1996). These results are in accordance with others TEMseries reporting morbidity of up to 4.5% in more than seven hundred patients and with our own experience (7%).…”
Section: Tem For Benign Lesionssupporting
confidence: 92%
“…In contrast the results reported using TEM show a recurrence rate between 3 and 7% with the 5.6% for the adenoma cases of our series pubished in 2004, being well in accordance with previous studies (Palma et al, 2004). The overall morbidity rate for conventional transanal surgery in reported series varies from 0 to 14.5%, compared with 6% reported in the largest series of a total of 318 adenomas treated by Mentges (Mentges et al, 1996). These results are in accordance with others TEMseries reporting morbidity of up to 4.5% in more than seven hundred patients and with our own experience (7%).…”
Section: Tem For Benign Lesionssupporting
confidence: 92%
“…1 However, these are major surgical procedures with associated complications and may be unsuitable for elderly, frail patients and unnecessary if the purpose of the intervention is to resect early benign lesions or achieve palliative symptom control. [2][3][4][5] In recent years, local treatment procedures have been developed to manage benign lesions and offer palliation in nonresectable tumors where the risks of open surgery would be unjustifiable. symptomatic control of anastomotic strictures without the risks of major surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Only three studies specifically addressed the outcome after TEM for low-versus high risk carcinomas. Mentges et al found recurrence rates after TEM for low-risk carcinomas (n 052) to be only 3.8%; however recurrence rates for high risk carcinomas (n 04) were not given, thereby prohibiting adequate comparison [35]. A retrospective, comparative study was performed by Heintz et al [29].…”
Section: Postoperative Tumor Selectionmentioning
confidence: 99%